Contributions to the Cognitive Study of Facial Recognition on Down Syndrome: A New Approximation to Exploring Facial Emotion Processing Style - Morales, Guadalupe Elizabeth; Lopez, Ernesto Octavio; Castro-Campos, Claudia; Charles, David Jose; Mezquita-Hoyos, Yanko Norberto (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Background: This paper aimed to explore the ability of people with Down syndrome (PWDS) in recognizing facial emotion by considering automatic cognitive processing levels of face recognition. Method: A sample of PWDS and participants with typical development (PWTD) participated in a set of two affective priming studies. In each study, participants had to categorize an emotional or neutral target face that was preceded by another emotional face. Stimuli presentation for each facial set (one face after another) was conducted by using an stimulus onset asynchrony (SOA) of 300 ms with the inter-stimulus interval (ISI) set at 50 ms. The first affective priming study manipulated emotion congruency between prime and target emotional faces to explore emotion classification abilities and to identify the cognitive mechanisms underlying automatic recognition of some emotional faces. The second study explored the effect that gender of a face has over categorization of facial emotion and difficulty in recognizing negative facial expressions. Results: The results strongly suggest that not all of the PWDS present difficulties in recognizing negative facial emotions. PWDS’ performance pattern in categorizing emotion was similar to that of PWTDs if they had to use broad classification categories (e.g., emotion vs. no emotion). However, differences between both samples occurred if PWDS had to use a specific category task (e.g., classification of happiness, sadness, etc.). Conclusions: At least two emotion information processing styles can be identified in PWDS. Methodological and theoretical implications for exploring the emotional capabilities of people with DS are discussed.